Needs Analysis for Developing an English Textbook for Doctoral Students in the Context of Buddhism: Enhancing Listening and Speaking Skills - Sarobol, Nopporn; Sudaruk, Phrakhrupalad Wisithakul (LEARN Journal: Language Education and Acquisition Research Network, 2025)
Needs analysis is essential for designing materials or textbooks, as it ensures that the content meets the specific needs and context of target learners. This research aims to explore the needs of doctoral students and stakeholders at a Buddhist university in Thailand to inform the design of an English textbook for doctoral students in listening and speaking skills. The study involved 155 doctoral students from various fields of study and 19 university administrative staff. Data were collected through a questionnaire focusing on the desired content and language functions for listening and speaking skills. The survey results identified topics and language functions related to Buddhism that met the needs of both students and additional stakeholders. Content areas such as traditions and festivals, education, science and technology, and social issues were rated highly by students and very highly by the administrative staff. In terms of language functions, listening for the main idea and details, making suggestions, giving instructions, expressing opinions, and providing reasons were perceived highly by students and very highly by administrative staff. These findings have implications for the development a textbook for an English course focused on Buddhism.